Chance and planning in Spanish elite soccer academy - Martinez-Santos, R.; Blanco-Villasenor, A.; Los-Arcos, A. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Soccer coaches must plan practice in accordance to different schedule units and in reference to a weekly competition structure. Furthermore, if they belong to an elite football academy they must take into account longer periods in terms of formative years (1). In this study we wanted to know how these possible sources of variance of coached practice occurred in a successful youth soccer school. Methods In total, 20 006 min of training in 272 sessions proposed by six coaches of the football academy of a Spanish Liga Club were analyzed (U-14 to U19 levels). Statistical procedures were run on SPSS 15.0, SAS 9.1.3 and Generalizability software by Ysewijin, (1996). Results & Discussion The internal logic of the exercises was the main planning factor. For instance, cooperation and opposition was not very affected by the proximity to the match during the week (table 1) even though differences were found in a 2 analysis. Different microstructural models of practice allowed to measure how these figures changed and to weight chance in our coaches` work when they included other playing constraints such as motor roles, space and scoring systems. Conclusion During formative years, the microstructure of the activities seems to be more relevant than the longer units of planning in the development of talent.